Research on wilderness area identification and distribution of spatial characteristics based on Boolean-multi-indicator evaluation approach —a case study of wilderness areas in Henan Province, China - Ren, Yaping; Wang, Shuyi; Cui, Bifeng; Ding, Yu; Cao, Runxiang (Frontiers in Environmental Science, 2025)
Under the background of global anthropocene and climate change, as a key spatial unit to maintain the function of native ecosystems, the study of precise identification and spatial distribution of wilderness is of great scientific value to enhance the effectiveness of rewilding practice. Taking the wilderness in Henan Province as a case study area, the thesis constructs the evaluation index system of wilderness in Henan Province by using the Boolean identification and multi-objective evaluation methods based on the analysis of the concept and connotation of wilderness, identifies the spatial distribution of wilderness in Henan Province, and analyzes the current status of protection and the vacancy of protection in Henan Province. The results of the study show that 1) in horizontal space, high-quality wilderness in Henan Province is mainly concentrated in the high-elevation and water-system peripheral areas in the north, west and south, while low-quality wilderness is dominant in the central plains and the periphery of the major transportation arteries. 2) In terms of vertical spatial distribution, the quality of wilderness increases with elevation, with a high proportion of low- and medium-quality wilderness in low-elevation areas, while high-quality wilderness is most distributed in high-elevation (800–1200 m) areas. 3) The area of wilderness in Henan Province is 20,052.60 km2, and the area of wilderness covered by nature reserves is only 3,017.40 km2, i.e., 84.95% of the existing wilderness is not included in the scope of protection, and there is a large area of protection gaps in the wilderness area, which urgently needs to be strengthened in terms of planning, reasonable protection and management. The results of this study can provide a theoretical basis for the development of scientific and reasonable wilderness protection policies in nature reserves, and are of significance in promoting the in-depth development of wilderness protection in Henan Province.